If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -1 = 7x + -13 Reorder the terms: -1 + 9x = 7x + -13 Reorder the terms: -1 + 9x = -13 + 7x Solving -1 + 9x = -13 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -1 + 9x + -7x = -13 + 7x + -7x Combine like terms: 9x + -7x = 2x -1 + 2x = -13 + 7x + -7x Combine like terms: 7x + -7x = 0 -1 + 2x = -13 + 0 -1 + 2x = -13 Add '1' to each side of the equation. -1 + 1 + 2x = -13 + 1 Combine like terms: -1 + 1 = 0 0 + 2x = -13 + 1 2x = -13 + 1 Combine like terms: -13 + 1 = -12 2x = -12 Divide each side by '2'. x = -6 Simplifying x = -6
| 8y-30=-3(y-1) | | 2x^2=x^3 | | 0=x+5.5x+9.5x+3.5 | | y=-0.90(20)+106 | | 0.5k-3.4=0.4 | | x+5x+7=0 | | -5-4(t-2)= | | 495+15p=720 | | 450=15*-3+b | | 450=-15*-3+b | | 450=-10*-3+b | | 450=-10*-13+b | | m+(2m+1.16)+(m+3)=12 | | 625=4x^2+x^2 | | 4-0.5x=-3 | | 18t+5(1-4t)= | | 9x^2-42x+40=0 | | 2y+3G=16 | | 4x^2-24=8x | | (4-z)(3z+8)=0 | | 9+7=710 | | 5n+6-6n+2=19 | | 5x^2=7x+2 | | 2a-4/2=-1 | | 16x^3-32x=0 | | x+2/7x^2-28 | | x+2/7^2-28 | | x+2/7x2-28 | | 4x-20+x+15+2x-10=180 | | 6r+29=5 | | (9-x)/2=13 | | 9-x/2=13 |